Impact of the calcium form of β-hydroxy-β-methylbutyrate upon human skeletal muscle protein metabolism. Issue 6 (December 2018) - Wilkinson, D.J.; Hossain, T.; Limb, M.C.; Phillips, B.E.; Lund, J.; Williams, J.P.; Brook, M.S.; Cegielski, J.; Philp, A.; Ashcroft, S.; Rathmacher, J.A.; Szewczyk, N.J.; et al.
Summary: Background & aims: β-hydroxy-β-methylbutyrate (HMB) is purported as a key nutritional supplement for the preservation of muscle mass in health, disease and as an ergogenic aid in exercise. Of the two available forms of HMB (calcium (Ca-HMB) salt or free acid (FA-HMB)) – differences in plasma bioavailability have been reported. We previously reported that ∼3 g oral FA-HMB increased muscle protein synthesis (MPS) and reduced muscle protein breakdown (MPB). The objective of the present study was to quantify muscle protein metabolism responses to oral Ca-HMB. Methods: Eight healthy young males received a primed constant infusion of 1, 2 13 C2 leucine and 2 H5 phenylalanine to assess MPS (by tracer incorporation in myofibrils) and MPB (via arterio-venous (A-V) dilution) at baseline and following provision of ∼3 g of Ca-HMB; muscle anabolic (MPS) and catabolic (MPB) signalling was assessed via immunoblotting. Results: Ca-HMB led a significant and rapid (<60 min) peak in plasma HMB concentrations (483.6 ± 14.2 μM, p < 0.0001). This rise in plasma HMB was accompanied by increases in MPS (PA: 0.046 ± 0.004%/h, CaHMB: 0.072 ± 0.004%/h, p < 0001) and suppressions in MPB (PA: 7.6 ± 1.2 μmol Phe per leg min −1, Ca-HMB: 5.2 ± 0.8 μmol Phe per leg min −1, p < 0.01). Increases in the phosphorylation of mTORc1 substrates i.e. p70S6K1 and RPS6 were also observed, with no changes detected in the MPB targets measured. Conclusions: These findings support the pro-anabolic properties of HMB via mTORc1, and show that despite proposed differences in bioavailability, Ca-HMB provides a comparable stimulation to MPS and suppression of MPB, to FA-HMB, further supporting its use as a pharmaconutrient in the modulation of muscle mass.